The gut microbiota features and the application value in predicting recurrent risks for gallstone patients who underwent laparoscopic cholecystectomy - Huiqiang Li; Weili Li; Xinzheng Liu; Jianhua Zhang; Chuncheng Lin; Shushen Ji; Huihui Jiang; Tao Wang; Zijian Su (mSystems)
ABSTRACT Gut microbiota is associated with gallstone occurrence and recurrence. But whether they can predict post-cholecystectomy choledocholithiasis recurrence needs to be investigated. From September 2020 to June 2021, a total of 100 symptomatic gallstone patients scheduled for laparoscopic cholecystectomy were enrolled in the Disease group in the Department of Hepatobiliary Surgery at Quanzhou First Hospital. Meanwhile, a total of 50 age- and sex-matched healthy controls were included in the Control group. Fecal specimens were collected from both groups and subjected to 16S rDNA sequencing (V3V4 region) for microbiologic analysis. After laparoscopic cholecystectomy, patients were followed up, and recurrent cases were recorded. Finally, a nomogram for predicting recurrent risks was built. The gut microbial diversity in the Disease group was significantly lower than that of the Control group (all P < 0.05). The Chao1 index of the recurrent group was remarkably lower than the control group (P < 0.05). Linear discriminant analysis (LDA) effect size (LEfSe) analysis showed that Phocaeicola dorei (LDA score = 4.2, P < 0.05) was the feature microbiota in the recurrent group. Logistic regression analysis showed that the composition of stones, the high abundances of P. dorei and Fusobacterium necrogenes were potential risk factors for recurrent choledocholithiasis, and a nomogram based on these factors demonstrated high accuracy and excellent calibration. This study has identified potential risk factors for recurrent choledocholithiasis and built a nomogram that can well predict recurrent risks for patients who undergo cholecystectomy, which might serve as a useful tool for patients’ stratification and post-surgery management.IMPORTANCEThis study identifies specific gut microbiome signatures of gallstone patients and indicates that reduced diversity and high abundances of Phocaeicola dorei and Fusobacterium necrogenes might be potential predictors for choledocholithiasis recurrence after cholecystectomy. By demonstrating a link between gut microbiota composition and post-surgical recurrence risk, it advances our understanding beyond simple association with predictive capability. The development of a nomogram incorporating these microbial markers provides a novel, clinically applicable tool for accurate risk stratification of patients undergoing cholecystectomy, therefore bridging the gap between microbial ecology and clinical practice. The significance of this study lies in that it aims to address a critical unmet need in gallstone disease management by offering a more cost-effective and non-invasive tool to improve long-term patient outcomes and pave the way for microbiome-targeted interventions.CLINICAL TRIALSThis study is registered with Chinese Clinical Trial Registry Center as ChiCTR2400090232.